Efficacy and Safety of Belimumab and Azathioprine for Maintenance of Remission in Antineutrophil Cytoplasmic Antibody–Associated Vasculitis: A Randomized Controlled Study. Issue 6 (16th April 2019) - Jayne, David; Blockmans, Daniel; Luqmani, Raashid; Moiseev, Sergey; Ji, Beulah; Green, Yulia; Hall, Leanne; Roth, David; Henderson, Robert B.; Merkel, Peter A.; ,
Abstract : Objective: To evaluate the safety and efficacy of belimumab as adjunctive therapy to maintain remission in antineutrophil cytoplasmic antibody (ANCA)–associated vasculitis (AAV). Methods: In this multicenter, double‐blind, placebo‐controlled study, patients with AAV (ages ≥18 years) were randomized 1:1 to receive azathioprine (2 mg/kg/day), low‐dose oral glucocorticoids (≤10 mg/day), and either intravenous belimumab (10 mg/kg) or placebo, following remission induction with rituximab or cyclophosphamide along with glucocorticoids. The primary end point was time to first protocol‐specified event (PSE), with first PSE defined as a Birmingham Vasculitis Activity Score (BVAS) of ≥6, presence of ≥1 major BVAS item, or receipt of prohibited medications for any reason, resulting in treatment failure (adjusted for ANCA type [proteinase 3 (PR3) or myeloperoxidase (MPO)], disease stage at induction, and induction regimen). Vasculitis relapse was defined as the PSE of either a BVAS activity score of ≥6 or receipt of prohibited medications for vasculitis. Changes in treatment practice led to truncation of the study population from ~300 patients to ~100 patients. Results: The intent‐to‐treat population totaled 105 patients with AAV, of whom 52 (40 with PR3‐ANCAs, 12 with MPO‐ANCAs) received placebo and 53 (41 with PR3‐ANCAs, 12 with MPO‐ANCAs) received belimumab; 27 of the patients were in rituximab‐induced disease remission, while 78 were in cyclophosphamide‐induced disease remission at baseline. Compared with placebo, treatment with belimumab did not reduce the risk of a PSE (adjusted hazard ratio [HR] 1.07, 95% confidence interval [95% CI] 0.44–2.59; P = 0.884) or vasculitis relapse (adjusted HR 0.88, 95% CI 0.29–2.65; P = 0.821). The overall rate of PSEs was low (11 [21.2%] of 52 patients receiving placebo, 10 [18.9%] of 53 patients receiving belimumab). Vasculitis relapse in the placebo group (n = 8) occurred independent of the induction regimen, disease stage, or ANCA type. All vasculitis relapses in the belimumab group (n = 6) occurred in patients who had PR3‐ANCA–associated vasculitis with cyclophosphamide‐induced disease remission. Adverse events occurred in 49 (92.5%) of 53 patients receiving belimumab and 43 (82.7%) of 52 patients receiving placebo, with no new safety concerns. Conclusion: Belimumab plus azathioprine and glucocorticoids for the maintenance of remission in AAV did not reduce the risk of relapse.